Agents, Institutions and Regions in Transition - Mark Mcgovern; Nurcan Temel Candemir (European Regional Science Association (ERSA), 2006)
The goal in this paper is to sketch a line of approach which may help order considerations of transition in various regions. Adjustments to change can occur in various ways, and they do. Dealing with such diversity is a challenge for analysts and policy makers in various sectors, regions and organisations. The regional analyst has particular issues in dealing with diversity both within and between regions for which existing tools and approaches provide only partial support. Agents are a key and dynamic part of any region. They combine perceptions, decision making and activity in pursuit of selected interests. Their actions have impacts, including on enterprise, societal and regional development. They stand in contrast to the markedly more limited decision maker and the determinable system. Their potential contribution to understanding transition and regional development appears little recognised. Of particular interest is the active agent who is sensitive to institutions and other contextual aspects. A socio-environmental rational agent (SERA) is presented. Its use provides a promising and more adequate way to advance understanding of regional transition issues. It is a more adequate formulation that the conventional self-interested rationalist (SIR). This is demonstrated conceptually and through a European case application. Institutions are recognised as a key part of a transition economy or society. Their explicit incorporation allows specific framing of key aspects of transition. Determinable solutions are not expected. Rather heuristics, simulations and specific methods as explored in this paper enable regional possibilities to be more clearly grasped.
Keywords: 330